ЎРТА АСР ЖАҲОН АДАБИЁТИ НАМУНАЛАРИНИНГ ЎЗБЕК ХАЛҚ ОҒЗАКИ ИЖОДИ НАМУНАЛАРИ БИЛАН ЎХШАШЛИКЛАРИ - Рузимов, Ш. (SCIENCE and SOCIETY, 2018)
The article deals with similarities and differences between the works of folklore of the West and the East. For example, the wars between tribes at the period of migration were displayed in German tribes’ folklore “Song about Hildebrant” which belongs to the eighth century and the author also shows the similarities with the “Shohnoma” by Firdausiy. In addition, similarities between an Ireland epos “Stealing a bull from Kualngen” and a Greek epos “Iliad” were shown too.
Keywords: feudalism; culture; divine; magic; courage; epos; exaggeration; bishop; faithfulness